The Relationship Between Organizational Commitment and Work Stress on Employees of Company: Hubungan Antara Komitmen Organisasi dengan Stres Kerja pada Karyawan Perusahaan - Anisyah Nur Fitria; Eko Hardiansyah (Academia Open, 2022)
The purpose of this study is to ascertain how workers' job stress and organizational commitment are related to each other in PT. Korea Tomorrow & Global Indonesia AMO Surabaya. The subjects in this study were employees of PT. Korea Tomorrow & Global Indonesia (AMO Surabaya) with a total of 85 subjects. The hypothesis in this study is that there is a negative relationship between organizational commitment and job stress on cigarette employees. This research uses saturated sampling method. This research data collection tool uses 2 psychological scales, namely the organizational commitment scale and the work stress scale. This data analysis uses product moment correlation. The results of this study show the results of the correlation coefficient showing the results of rxy 0.624 with a significant difference of 0.000 0.05. This means that the research hypothesis is accepted. Employees who work in the cigarette industry experience less stress at work when organizational commitment is strong, while the opposite is true when organizational commitment is low. This demonstrates how organizational commitment reduces workplace stress by 39%. Highlights: The study examines the relationship between job stress and organizational commitment among employees of PT. Korea Tomorrow & Global Indonesia (AMO Surabaya) in the cigarette industry. The research findings support the hypothesis of a negative relationship between organizational commitment and job stress in this context. The study highlights the significance of organizational commitment in reducing workplace stress for employees, with a demonstrated reduction of 39%. Keywords: Job stress, Organizational commitment, PT. Korea Tomorrow & Global Indonesia, AMO Surabaya, Cigarette employees